Analisis Pengaruh Intensitas Penerangan Pada Laboratorium Dan Bengkel Jurusan Teknik Elektro - Parera, Lory Marcus; Tupan, Hendrik Kenedy; Puturuhu, Victor (JURNAL SIMETRIK, 2018)
Lighting is one of the most important components in planning a building. To do all the activities that exist in the room of a building then needed a sufficient intensity of lighting, so that it can be carried out with maximal especially related to work practices conducted in the laboratory for the purposes of teaching and learning process. Lighting in the room when viewed from the quality is a strong illumination or lighting level is required where for different types of activities will require different levels of illumination. The results of this study is based on the use of light intensity in the laboratory and workshop through a measurement of the intensity of room lighting using SNI 16-7062-2004 standard and calculate the electrical energy it uses. Measurement of landing intensity was measured using lux meter measuring instrument. Measurements are done at 09.00, 12.00 and 15.00. The room is in accordance with the standard of environmental health requirements of office and industrial work with an area of 118.80 m2 has a lighting intensity (E) of 183.82 lux. While the intensity of illumination (E) 20.85 - 85.44 lux is recommended for the addition of the number of points of light